2010
DOI: 10.1177/0192513x10365834
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know About the Link Between Marriage and Health?

Abstract: Married people enjoy better physical and mental health than those who are not married (Schoenborn, 2004), and the children of married parents experience better health than do children raised in single-parent families (for reviews,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 86 publications
3
107
0
4
Order By: Relevance
“…Longitudinal studies are required to clarify the direction of causation of identified relationships, for example, whether the poor health of the divorced/separated is because being married 'protects' against illhealth or ill-health 'selects' people out of marriage (Koball et al, 2010). We use a measure of income based on self-reports of all household members, which may lack reliability.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…Longitudinal studies are required to clarify the direction of causation of identified relationships, for example, whether the poor health of the divorced/separated is because being married 'protects' against illhealth or ill-health 'selects' people out of marriage (Koball et al, 2010). We use a measure of income based on self-reports of all household members, which may lack reliability.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…Marriage has long been suggested to have a protective effect on health (including survival; for reviews see Koball et al 2010;Rendall et al 2011). Such a causal effect is said to result from both economic advantages and social support inherent in a marriage.…”
Section: Partnership and Adult Healthmentioning
confidence: 99%
“…In a longitudinal study, Joung et al (1998) showed that married people who reported various health complaints or chronic conditions were significantly more likely to become divorced than people without these health problems. More recently Koball et al (2010) confirmed this health selection into marriage using data on African Americans. Similarly, a longitudinal study by Brockmann and Klein (2004) provided empirical evidence that marriage, especially a long-lasting first marriage, had positive health effects which accumulated over time and thus promoted longevity.…”
Section: Household Position and Adult Healthmentioning
confidence: 77%